우리나라 청소년의 고카페인 에너지 음료 섭취와 자살생각과의 관련성 - 박정훈; 함명일; 김선정; 민인순; Park, Jeong Hun; Hahm, Myung-Il; Kim, Sun Jung; Min, In Soon (韓國學校保健學會誌, 2016)
Purpose: The purpose of this study is to examine the association between consuming high-caffeine energy drinks and suicidal ideation in Korean adolescents. Methods: This study used data drawn from the 2015 Korea Youth Risk Behavior Web_Based Survey. The data of 66,068 students in total (33,374 middle school students and 32,694 high school students) were included in the analysis. The $x^2$ test, univariate and multivariate logistic regressions were conducted with the use of SAS 9.3. Results: Adjusted for the variables associated with suicidal ideation, multivariate logistic regression revealed that consuming highly caffeinated energy drinks had a significant effect on suicidal ideation (middle school students, 1~2 times per week: OR=1.24, 3~4 times per week: OR=1.88, 5~6 times per week: OR=2.20, everyday: OR=2.66, high school students, 1~2 times per week: OR=1.26, 3~4 times per week: OR=1.84, 5~6 times per week: OR=2.42, everyday: OR=3.89). Conclusion: This study strongly suggests adolescents be provided with health education and information about consuming an adequate amount of high-caffeine energy drink and the drink's side effects. In addition, regulations and polices on high-caffeine drink intake should be implemented.